The Different Levels of Understanding among Indonesians on Home Care Services for Stroke Patients - Chayati, Nur; Guru, Yustina Yantiana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Treating patients after a stroke requires long-term home care, but it is not accessible by all Indonesians. Therefore, this study examined stroke patients' understanding of home care and its factors. A comparative design with a survey approach was employed, and the respondents were from Western (n=193) and Eastern Indonesia (n=193). The data were analyzed using the Pearson Chi-square test with a significant level of 5% and three categories of knowledge level. Indonesians have a good understanding 67.3% on home care. Furthermore, Western Indonesians were more well-informed compared to Eastern Indonesians. However, a significant relationship between the level of understanding in these two regions was associated with education, gender, and exposure to information about home care (p less than 0.05). This inequality influenced their knowledge about home care services (p=0.000) since the information is not well-distributed. These findings imply that the distribution of information about home care is not evenly shared throughout Indonesia. This is against the contention that home care is a significant health service to reach remote communities. It is suggested that the available media can be used to socialize home care services to the Eastern Indonesian region. Abstrak: Pengobatan pasien pasca stroke memerlukan waktu perawatan di rumah yang cukup lama, namun tidak semua penduduk Indonesia mampu melakukannya. Untuk itulah, penelitian ini bertujuan untuk menganalisis pemahaman pasien stroke terhadap konsep home care dan faktor-faktor yang mempengaruhinya. Penelitian merupakan studi komparatif dengan pendekatan survey, dengan responden dari penduduk Indonesia Barat (n=193 responden) dan Indonesia Timur (n=193 responden). Data dianalisis dengan Pearson Chi-Square dengan tingkat signifikansi 5% dan dikelompokkan dalam tiga kategori tingkat pengetahuan. Hasil menunjukkan bahwa sebanyak 67,3% penduduk Indonesia pemahamannya terhadap home care adalah baik. Lebih jauh lagi, penduduk Indonesia Barat terbukti lebih paham tentang home care dibanding Indonesia Timur. Pengetahuan tentang home care berkorelasi secara signifikan dengan tingkat pendidikan, jenis kelamin, dan paparan informasi tentang home care (p kurang dari 0,05). Perbedaan tingkat pengetahuan antara dua wilayah Indonesia ini (p=0,000) terjadi karena informasi tidak tersampaikan dengan baik. Penelitian ini berimplikasi bahwa distribusi informasi tentang home care belum diberikan kepada seluruh warga Indonesia. Hal ini sangat berdampak signifikan mengingat home care adalah jenis pelayanan kesehatan yang mampu menjangkau wilayah terpencil. Disarankan bahwa keberadaan media dapat digunakan untuk mensosialisasikan tentang layanan home care bagi wilayah Indonesia Timur.